194k views
3 votes
Evaluate each expression for the given value of the variable.
x + 2x - x - 1; x = 2

2 Answers

5 votes
The Equation is

x + 2x - x - 1 = 0

The Value of x = 2 ,

Putting in Equation , we get

2 + (2 Ă— 2) - 2 - 1 = 0

2 + 4 - 2 - 1 = 0

6 - 3 = 0

The Answer is 3
User Pihentagy
by
7.1k points
4 votes

x + 2x - x - 1

  • Substitute 2 for x into the expression.

(2) + 2(2) - (2) - 1

  • Multiply 2 * 2 first.

(2) + (4) - (2) - 1

  • Solve from left to right.
  • (2 + 4) - 2 - 1 = 6 - 2 - 1

6 - 2 - 1

  • Solve from left to right.
  • (6 - 2) - 1 = 4 - 1

4 - 1 = 3

Your answer is 3.

User MCattle
by
6.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.